Sustainable Development and the 2030 Agenda: reflections on the relationship between society and nature (Terr@ Plural, 2022)
Our objective is to understand the relationship between society and nature and the concept of sustainable development present in the UN's Agenda 2030 document, from a dialogue between the critical and decolonial perspectives. To this end, we divide this discussion into three moments: first, we address the relationship between society and nature, then, we analyze the concept of sustainable development, conducting a dialogue with the decolonial perspective and the Latin American territorial problem. In the third moment we make considerations in view of the challenges to be faced to build sustainable development in Latin America: the possibility of producing knowledge from the bottom up; with and from the people and places; recognizing the pluriversity and multidimensionality of the society-labor-nature-humanity relations; thinking of diverse forms and possibilities of sustainable development.
Keywords: Decoloniality, Latin America, Pluriversity, Society & Nature.